Influence of water depth variation on the hydrodynamics of deep-water mooring characteristics. (15th November 2015) - Lin, Zi; Sayer, P.
Abstract: This paper studies the behaviour of a mooring system, in water depths from 300 m to 3000 m, using an indirect time-domain method. The boundary element method and lumped mass method are used to investigate the floating body hydrodynamics and mooring line characteristics, respectively. Results from coupled analysis are compared with experimental data in intermediate water depth. The results from coupled low frequency (LF) and fully coupled analysis are compared and discussed. Results from parametric studies are compared to offer guidance to mooring system designers on the suitability of particular approaches. Highlights: The modelling is validated with available experimental data. Focusing on moderate to ultra-deep water depths (~300–3000 m), key parameters and coupling effects are investigated. Based on a parametric study, guidance on mooring system design is put forward.